Network Dynamics of Attention During a Naturalistic Behavioral Paradigm - Weber, René; Alicea, Bradly; Huskey, Richard; Mathiak, Klaus (Frontiers in Human Neuroscience, 2018)
This study investigates the dynamics of attention during continuous, naturalistic interactions in a video game. Specifically, the effect of repeated distraction on a continuous primary task is related to a functional model of network connectivity. We introduce the Nonlinear Attentional Saturation Hypothesis (NASH), which predicts that effective connectivity within attentional networks increases nonlinearly with decreasing distraction over time, and exhibits dampening at critical parameter values. Functional Magnetic Resonance Imaging (fMRI) data collected using a naturalistic behavioral paradigm coupled with an interactive video game is used to test the hypothesis. As predicted, connectivity in pre-defined regions corresponding to attentional networks increases as distraction decreases. Moreover, the functional relationship between connectivity and distraction is convex, that is, network connectivity somewhat increases as distraction decreases during the continuous primary task, however, connectivity increases considerably as distraction falls below critical levels. This result characterizes the nonlinear pattern of connectivity within attentional networks, particularly with respect to their dynamics during behavior. These results are also summarized in the form of a network structure analysis, which underscores the role of various nodes in regulating the global network state. In conclusion, we situate the implications of this research in the context of cognitive complexity and an emerging theory of flow during media exposure.